2022
DOI: 10.1007/s00438-022-01865-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community composition associated with early developmental stages of the Indian white shrimp, Penaeus indicus

Abstract: Gut microbiota is known to in uence the physiology, health, nutrient absorption, reproduction, and other metabolic activities of aquatic organisms. Microbial composition can in uence intestinal immunity and are considered as health indicators. Information on gut microbial composition provides potential application possibilities to improve shrimp health and production. In the absence of such information for Penaeus indicus, the present study reports the microbial community structure associated with its early de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…A clear dynamic of the active microbial diversity associated with the larvae was evidenced throughout the whole rearing (Figures 3 and 4), as previously shown for the microbial diversity of other penaeids shrimp larvae: Penaeus indicus [46] or P. vannamei [3,47,48]. Strikingly different microbial compositions were observed between D1 (nauplii) and D2 (zoea), between D5 (zoea) and D7 (mysis) with a transition on D6 (zoea), along with the three distinct clusters underlined by the NMDS (Figure 3), regrouping larvae microbiota samples according to the larval stage.…”
Section: Discussionsupporting
confidence: 79%
“…A clear dynamic of the active microbial diversity associated with the larvae was evidenced throughout the whole rearing (Figures 3 and 4), as previously shown for the microbial diversity of other penaeids shrimp larvae: Penaeus indicus [46] or P. vannamei [3,47,48]. Strikingly different microbial compositions were observed between D1 (nauplii) and D2 (zoea), between D5 (zoea) and D7 (mysis) with a transition on D6 (zoea), along with the three distinct clusters underlined by the NMDS (Figure 3), regrouping larvae microbiota samples according to the larval stage.…”
Section: Discussionsupporting
confidence: 79%
“…Vibrio and Psychrobacter were barely detected in Group L. SS-128, while both were detected in the control group (Vibrio: 0.72%, 0.72%, 1.53%; Psychrobacter : 0.50%, 0.28%, 0.50%) and luxS -mutant group (Vibrio: 1.31%, 0.29%, 0.47%; Psychrobacter : 1.11%, 0.90%, 0.90%). The study by Vinay et al (2022) showed that Proteobacteria is of the most abundant in all of the developmental stages [ 48 ]. Actinobacteria , Proteobacteria , and Bacteroidota are reported to be the largest relative abundance of bacterial phyla of Pacific White shrimp Penaeus vannamei during an outbreak of white feces disease [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, some microbiotas are helpful to digestion, absorption and utilization of nutrient, and the regulation of immune system, whose composition has an important impact on intestinal health [61] . Some studies indicated that the predominant bacterial phyla in shrimp digestive tract were Firmicutes, Proteobacteria and Bacteroidetes [ 13 , 62 , 63 ]. In the present study, Firmicutes, Proteobacteria and Bacteroidetes were the predominant bacterial phyla in the digestive tract of juvenile shrimp in all treatments, while at genus level, the bacterial composition of all the treatment were dominated by Muribaculaceael, Lactobacillus and Bacteroides .…”
Section: Discussionmentioning
confidence: 99%